Peninjauan Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Karyawan Secara Kuantitatif pada PT Citra Lentera Indonesia - Azis, Abdul; Arif, Fathan (STIE AUB Surakarta, 2025)
This study aims to review the effect of work motivation and discipline on employee performance at PT Citra Lentera Indonesia, either partially or simultaneously. This study uses a quantitative approach. The population in this study were all employees, totalling 65 employees. The sampling technique uses a saturated sample technique in which the sample in this study is 65 employees. The type of data used is primary and secondary. The data analysis technique used is descriptive statistical analysis, data instrument testing, classic assumption testing, simple and multiple linear regression testing, hypothesis testing through t-test and F-test, as well as correlation and determination coefficient tests. The results showed that partially motivation had a positive and significant effect on employee performance. tcount value 6,460 > 2,002 ttable value with a significant value of 0.000 <0.05. Simultaneous testing shows that motivation and work discipline simultaneously have a positive and significant effect on employee performance, this is indicated by the Fcount value of 31,450 > 3,159 Ftable value with a significance value of 0.000 <0.050. The R-Square value of 0,555 indicates that motivation and work discipline affect employee performance by 55,5% and the rest are influenced by other variables.